2006
DOI: 10.1128/jvi.00153-06
|View full text |Cite
|
Sign up to set email alerts
|

A 38-Amino-Acid Sequence Encompassing the Arm Domain of the Cucumber Necrosis Virus Coat Protein Functions as a Chloroplast Transit Peptide in Infected Plants

Abstract: Experiments to determine the subcellular location of the coat protein (CP) of the tombusvirus Cucumber necrosis virus (CNV) have been conducted. By confocal microscopy, it was found that an agroinfiltrated CNV CP-green fluorescent protein (GFP) fusion targets chloroplasts in Nicotiana benthamiana leaves and that a 38-amino-acid (aa) region that includes the complete CP arm region plus the first 4 amino acids of the shell domain are sufficient for targeting. Western blot analyses of purified and fractionated ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 47 publications
6
36
3
Order By: Relevance
“…Such studies should therefore assist in future work aimed at elucidating the in vivo assembly process. In addition, as suggested in a previous study, specific CNV CP sequences along with specific host factors have been implicated in the CNV assembly/disassembly pathway (41). It is anticipated that the studies described here should facilitate further analyses of these aspects of the assembly process.…”
Section: Vol 82 2008supporting
confidence: 61%
See 1 more Smart Citation
“…Such studies should therefore assist in future work aimed at elucidating the in vivo assembly process. In addition, as suggested in a previous study, specific CNV CP sequences along with specific host factors have been implicated in the CNV assembly/disassembly pathway (41). It is anticipated that the studies described here should facilitate further analyses of these aspects of the assembly process.…”
Section: Vol 82 2008supporting
confidence: 61%
“…Virus particles were denatured and electrophoresed through NuPage BisTris gels (Invitrogen) essentially according to the manufacturer's recommended conditions. Proteins were blotted onto polyvinylidene difluoride (PVDF) membranes (Bio-Rad) and probed with a mixture of three polyclonal antibodies known to be specific to the CNV S-and P domains (41) c The approximate Tϭ3:IS:Tϭ1 particle ratio was assessed by TEM of uranyl acetate-stained particles. At least 250 particles were examined using several different areas of one or more TEM grids.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…Coat protein-GFP fusion protein constructs have also been shown to target mitochondria, wherein 38 aa of the N-terminal region of the CP are sufficient for mitochondrial targeting (39). We have previously shown that 3 specific cleavage events occur during chloroplast targeting of the CNV CP (38,39) (Fig. 1B).…”
mentioning
confidence: 96%
“…Approximately 1 to 5% of the CNV CP in a CNV-infected cell is present in chloroplasts (38). Although the biological significance of chloroplast targeting is not known, it was suggested that CNV particles may uncoat on the cytoplasmic side of the chloroplast outer membrane as CP subunits are reeled into the chloroplast during CP uptake (38).…”
mentioning
confidence: 99%
See 1 more Smart Citation